Parental Involvement and Self-regulated Learning: The Case of Arab Learners in Israel - Saada, Nabil (Journal of Interdisciplinary Studies in Education, 2022)
Parental involvement is a reliable predictor of students' school behavior. Findings indicate that the relationship between parental involvement and self-regulated learning is mediated by cultural and socio-economic background. Most studies in this area come from anglophone countries. The current study examined the generalizability of the correlation between the two concepts in a non-Western culture. Survey data from 312 Arab adolescent learners in Israel revealed that students who reported experiencing PI also reported engaging in SRL. The findings indicated that emotional/motivational support and parenting behaviors related to schooling are strong predictors of SRL. The results underpin parents' importance in the middle-school age and support previous evidence for the significance of PI in students' SRL in all cultural contexts.